Geodiversity and Geoheritage Potential of Basalt Caves in Girimulyo Village, East Lampung, Indonesia: A Mixed-Method Assessment Approach - Bilal Al Farishi; Syifa Faranabila; Gilbert Prima; Zatalini Syadni Rahadian; Happy Christin Natalia; Nono Agus Santoso; Risky Martin Antosia (Yayasan Ghalih Pelopor Pendidikan, 2025)
This study evaluates the geodiversity and geoheritage potential of basalt caves in Girimulyo Village, East Lampung, Indonesia, focusing on scientific, educational, tourism, and degradation risk values. Eight caves, including Pandan 1, Pandan 2, Kelelawar, and Kubah, were assessed through field observations, stakeholder interviews, and visual documentation. Pandan 1 Cave demonstrated the highest potential with an average score of 281.67, attributed to its unique geological features, including A’a lava, pahoehoe lava, and bread crust textures. Kelelawar Cave’s biodiversity, particularly its bat habitat, highlights its suitability for ecotourism, while Kubah Cave attracts adventure tourists with its columnar joint formations. Jagung Cave was identified as the most vulnerable to degradation, scoring 295 due to agricultural activities nearby. Conservation measures, visitor management, and sustainable tourism practices are essential to protect these geoheritage sites. Recommendations include developing visitor pathways, educational tours, and geotourism infrastructure. Limitations include reliance on visual assessments for degradation risk and limited cave access. Future research should include geotechnical analysis and explore the socio-economic impact of geotourism on local communities. The findings provide a framework for sustainable geotourism, balancing conservation, education, and tourism growth.